G235(P) Holes in the Net: A study of safety netting provided by paediatric trainees in the Emergency Department. (27th April 2016) - Jacob, H; Cohen, K; Lloyd, B; Raine, J
Abstract : Aims: Paediatric safety netting (SN) involves providing information to children and families about their illness, typically upon discharge from the Emergency Department (ED). Effective SN can reduce unnecessary re-attendances and encourage appropriate re-attendance, thereby reducing morbidity and mortality. Little is known about the SN advice clinicians give and how well this is documented in the medical notes. This study assessed SN advice, comparing paediatric trainees' perception of the SN advice they provide, with SN documentation in the medical notes. Methods: First, all the junior doctors in general paediatrics at one district general hospital were invited to complete an anonymised questionnaire about their SN practices. Second, a retrospective case notes review was conducted of 100 consecutive ED attendances seen by the paediatric team in the three weeks before the questionnaires were distributed. SN documentation was assessed. The perceived and documented SN practices were compared. Results: A total of 17/25 (68%) trainees completed the questionnaire. Of these, 11/17 (65%), reported SN at least 80% of the time. The mean age of children attending was 2 years 7 months (range 1 month -1 5 years). 39% of patients received no specific SN advice. The table compares reported SN practice with that documented in the medical notes. Conclusion: Trainees' own assessment identified a considerable gap between the SN that they report undertaking and the ideal, which would be SN encompassing many of the areas mentioned in the questionnaire. Trainees perceived that they provided SN advice more commonly than it was documented in the notes. This may be because they provided verbal SN advice without documenting it or because in practice SN procedures were poor, despite the clinical and medico-legal imperative for adequate SN and documentation. Our study highlights the need to improve training for junior doctors on SN and its documentation. Further work will evaluate how a checklist may improve SN documentation in the ED.